2011
DOI: 10.1638/2009-0185.1
|View full text |Cite
|
Sign up to set email alerts
|

Penicilliosis in an African Grey Parrot (Psittacus erithacus)

Abstract: Penicillium mycosis, or penicilliosis, is rare in animals. This report describes the clinical signs and pathological, immunohistochemical, and biomolecular findings in a case of avian penicilliosis in a Congo African grey parrot. On gross necropsy, pyogranulomatous changes were identified in the lung, liver, and kidney. Histopathology demonstrated periodic acid Schiff-(PAS) and Grocott-positive hyphae in these tissues. Immunohistochemistry confirmed the genus of the fungus and polymerase chain reaction (PCR) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Mycotic infections in African grey parrots including pulmonary aspergillosis by Aspergillus fumigatus (Oca et al, 2022), cryptococcosis (Schunk et al, 2017), mucormycosis (Desmidt et al, 1998, and penicillosis (Lanteri et al, 2011) have been reported, so the gray parrot is thought to be highly susceptible to mycotic infections (Arné et al, 2021). Clinical signs of avian aspergillosis may be nonspecific, with hyperthermia, weight loss, anorexia, and polydipsia, and may be directly related to the affected systems, such as coryza, unproductive cough, wheezing on auscultation, and dyspnea in cases of respiratory infections (Arné et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Mycotic infections in African grey parrots including pulmonary aspergillosis by Aspergillus fumigatus (Oca et al, 2022), cryptococcosis (Schunk et al, 2017), mucormycosis (Desmidt et al, 1998, and penicillosis (Lanteri et al, 2011) have been reported, so the gray parrot is thought to be highly susceptible to mycotic infections (Arné et al, 2021). Clinical signs of avian aspergillosis may be nonspecific, with hyperthermia, weight loss, anorexia, and polydipsia, and may be directly related to the affected systems, such as coryza, unproductive cough, wheezing on auscultation, and dyspnea in cases of respiratory infections (Arné et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was documented that bamboo rats and the soil from their burrows were important enzootic and environmental (natural) reservoirs of P. marneffei [ 148 , 149 , 150 ]. However, penicilliosis is still rare in animals [ 151 ].…”
Section: Penicilliosismentioning
confidence: 99%
“…The section of the lung parenchyma presented grossly normal areas scattered with yellowish septa and yellow material inside the bronchial and tracheal lumen. The foci were alike in the thoracic cranial air sacs [ 151 ].…”
Section: Penicilliosismentioning
confidence: 99%
See 1 more Smart Citation